Interest of 11th Grade Students in Mathematics Learning Media Assisted by Microsoft PowerPoint - Fitria, Rani Laylatul; Sudiarti, Mira; Suyanto, Slamet; Zafrullah, Zafrullah (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
Learning media has an important role in providing new variations in learning, especially in learning mathematics. The purpose of this research is to describe students' interest in learning using Microsoft PowerPoint on statistics in grade 11. This research is a descriptive quantitative study with a sample of 24 students from SMK Migas Bumi Melayu, Riau, Indonesia. The research instrument used was a non-test instrument in the form of a learning interest questionnaire with 20 statements consisting of 5 aspects. The data analysis technique used is quantitative descriptive analysis. The final results show that the feeling of pleasure category is at 81.67%. For the category of interest in learning is at 81.46%. While in the category of attention to learning is at 79.79%. And for the category of involvement in learning is at 80.42%. Based on the results of the research that has been described per aspect, almost all categories of student learning interest in the questionnaire are classified as very good, so that learning media shows a positive response from students to student learning, with a percentage of 80.83% in the very good category.